Computer-based modeling of soft tissues for medical and gis applications - Rana, Mohammad Azam (2005)

(untitled)
The advances in medical imaging, beginning from the discovery of X-rays have nowadays opened new perspectives for improvements in the area of computer assisted surgical planning. Meanwhile, modern medical imaging techniques, such as Computer Tomography (CT) and Magnetic Resonance Imaging (MRI), are widely-used for diagnostic and require 3D models of human anatomy for visualization purposes. 3D body models provide the information on the geometrical disposition of different anatomical structures. In craniofacial surgery, there is a great demand for efficient computer assisted methods, which could enable flexible, accurate and robust simulations for the realistic prediction of postoperative appearance. The computer assisted surgical planning has many advantages in comparison with conventional planning systems. Once the virtual model of a patient is generated, various case scenarios of the surgical impact and their outcomes can be extensively studied. Better preparation, shorter operation time, lower costs are the immediate benefits. Since the improvement of the patient’s aesthetics is one of the main aims in craniofacial surgery, the realistic prediction of the patient’s postoperative appearance is an important feature of the surgical planning system, giving the surgeon unique feedback during the planning stage. The topic of soft tissue modeling has been the subject of intensive investigations of many research groups within the last few decades. Because of the complexity of soft tissue behavior and diverse types of application fields, a wide spectrum of approaches has been developed for their realistic simulation. This paper presents various approaches developed for simulation of human soft tissues that are being applied in the area of medical and GIS applications.